Program Design Implications from International Business Majors' Goals Before and After Undergraduate Study. Issue 2 (3rd July 2022) - Routon, P. Wesley; Hartley, Phillip; Torres, Luis
ABSTRACT: Understanding students' post-graduation goals is important because it aids faculty and administrators in course and program design, mentoring, and generally serving students. Using a sample of almost 513, 000 undergraduates from more than 600 colleges and universities, we examine goals and plans of international business majors. Students were surveyed near matriculation and graduation. First, responses of international business majors are presented. Then, goals of these students are compared to others, both other business majors and non-business majors. Finally, logistic regression analysis is used to estimate how different the typical goals of international business majors are from other students after controlling for demographics, background, and collegiate experiences. Nine different post-graduation goals are examined, including those pertaining to further education, future job characteristics, travel, personal wealth, and altruistic aspirations. Results indicate that IB students, on average, place a high level of importance on numerous goals, more so than other business students in most cases. The impacts of IB education on student goals are found to vary little across the type of institution attended. Misalignment between IB students' goal prioritization and careers in the field motivates a discussion of areas with potential for improvement in IB programs.